Blood pressure variation and hypertension rates in a pre-modernized Bedouin population: data from tribes of the Sinai Peninsula (Egypt) - Hani Monk-Vitelson; Israel Hershkovitz; Eugene Kobyliansky (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
During the 20th century Bedouin society has shifted from semi-nomad pastoralism toward a more Western life style, whilst accumulating risk factors for life threatening diseases. This is evident from recent reports of hypertension and obesity in Bedouin groups.In face of this epidemiological transition, it is important to document blood pressure (BP) values and related anthropometrics of Bedouin tribes prior to considerable exposure to modernization. The Towara tribes of the Sinai Peninsula represent traditional Bedouin subsistence and culture.The Towara sample includes 318 men and 91 women, age 17 up to 85 years. Mean BP values of Towara men and women are 121/81 and 111/76, respectively. The overall rates of hypertension (HTN, defined as the percent of persons with systolic BP >/= 140 and/or diastolic BP >/= 90 mmHg) are 12% for males and 4% for females. BMI is 20 kg/m2 for both sexes. Blood pressure values and HTN rates of the Towara males and females are found to be low when compared to other Bedouin and Arab groups of the Middle East.Inter-tribal comparison considers only young adults: ages 20-39 years for men and 17-39 for women. Females of the Muzeina tribe have exceptionally low BP values: 108/76 mmHg, while Muzeina males (BP: 122/80 mmHg) are not distinguishable from other Towara groups. HTN rates in the 4 male tribal groups range between 6% and 20%.No consistent age-dependent increase is evident for males in either BP or HTN rates, although for both traits the youngest Towara men (17-19 years) have lower values than the oldest group (50+): 117/79 vs. 125/86, and 5% vs. 19%. Female samples do not allow for effective comparison, however only 3 Towara women were found to have HTN.The low values of BP and HTN rates reflect the traditional subsistence of Towara population and can serve as a reference for comparison along the modernization process.